The Role of Values in Decision-Making for National Development Planning (a study in light of legal orders in Poland and Norway) - Kokocińska, Katarzyna (Review of European and Comparative Law, 2023)
The issues discussed in this paper relate to the axiological justification of planning decisions as part of development policy pursued by public authority bodies, using the example of Polish and Norwegian planning systems. This study derived from the premise that the contemporary model of planning for socio-economic development is crucially significant in terms of organizing the activities of public administration that aim to meet socio-economic needs. In addition to values, the article also identifies legal institutions through which the values in question may be integrated in planning decisions for the development pursued with public participation.